Analisis Penggunaan “Gadget” terhadap Prestasi Siswa Kelas X di SMK YPK Imanuel Kota Sorong - Simson Mambraku; Muhammad Ali Kasri; Saharudin Saharudin (Router : Jurnal Teknik Informatika dan Terapan, 2025)
This research aims to analyze the problem or impact of using gadgets on the achievement of student X at YPK Imanuel Vocational School, Sorong City. The research method uses a qualitative approach using case studies. Data was collected by observation, interviews and documentation. The sample was determined using the "Purposive Sampling" technique. The subjects of this research were 11 students of class X multimedia 1 and 10 multimedia students. The results of this research show that the use of gadgets does not have a completely negative impact on student achievement, but rather provides positive things that students can do, such as making it easier for students to do assignments, being interactive and making it easier for students to find information. This can be seen from the results of research conducted by researchers on class , images and animations that can increase students' interest and understanding of the subject.